Facile synthesis of mordenite zeolites from bamboo leaves ash for acetalization of benzaldehye and glycerol using non-microwave instant heating - Gong, Jiang-Tian (Elsevier, 2024)
Backgrounds: Bamboo leaves ash (BLA) is a cheap and sustainable silica source but under-utilized. In this work, mordenite zeolites with various morphologies synthesized from BLA are reported. Methodology: Our strategy involves merely mixing of silicate and aluminate solutions where parametric crystallization study successfully captured three mordenite synthesis recipes. The prepared solids are then characterized with XRD, SEM, XRF, FTIR, TGA/DTG, N-2 sorption and TPD-NH3 before their catalytic behavior is tested in acetalization . Significant findings: Mordenites with three distinct shapes (nanostick, intergrown bulky ball, nanorod) are successfully synthesized via parametric crystallization study. Some mordenite zeolites contain hierarchical micro/mesoporosity which is beneficial in acetalization of benzaldehye and glycerol. The nanorod-like mordenite is the best catalyst (80.2 +/- 2.4 % conversion, 54.4 +/- 0.3 % selective towards 2-benzyl-4-hydroxymethyl-1,3-dioxolane) and its catalytic performance is better than those of classical homogeneous and zeolite catalysts with high recyclability.